2019
DOI: 10.1158/2326-6066.cir-18-0466
|View full text |Cite
|
Sign up to set email alerts
|

IL15 Enhances CAR-T Cell Antitumor Activity by Reducing mTORC1 Activity and Preserving Their Stem Cell Memory Phenotype

Abstract: Improvements in the quality and fitness of chimeric antigen receptor (CAR)-engineered T cells, through CAR design or manufacturing optimizations, could enhance the therapeutic potential of CAR-T cells. One parameter influencing the effectiveness of CAR-T cell therapy is the differentiation status of the final product: CAR-T cells that are less differentiated and less exhausted are more therapeutically effective. In the current study, we demonstrate that CAR-T cells expanded in IL15 (CAR-T/IL15) preserve a less… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
224
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 312 publications
(253 citation statements)
references
References 53 publications
9
224
1
Order By: Relevance
“…Recently, Ghassemi et al reported that decreasing the time of in vitro T cell expansion increased its antitumor activity in vivo, and lower doses of CAR T cell were able to control leukemia growth (25). This report goes in line with the literature, showing that considerable T cell differentiation occur after in vitro expansion, with less differentiated, central memory-like T cells being associated with improved antitumor activity in preclinical models (26)(27)(28) and patients (29). In this proof-of-principle paper, we take this concept one step further and show that, by using SB transposon system and electroporation-based gene delivery, CAR-T cells can be generated and directly used for therapy, without the need of ex vivo activation and expansion protocols.…”
Section: Introductionsupporting
confidence: 68%
“…Recently, Ghassemi et al reported that decreasing the time of in vitro T cell expansion increased its antitumor activity in vivo, and lower doses of CAR T cell were able to control leukemia growth (25). This report goes in line with the literature, showing that considerable T cell differentiation occur after in vitro expansion, with less differentiated, central memory-like T cells being associated with improved antitumor activity in preclinical models (26)(27)(28) and patients (29). In this proof-of-principle paper, we take this concept one step further and show that, by using SB transposon system and electroporation-based gene delivery, CAR-T cells can be generated and directly used for therapy, without the need of ex vivo activation and expansion protocols.…”
Section: Introductionsupporting
confidence: 68%
“…Decreased mTORC1 activity due to IL15, which is used to expand CAR-T cells, also enhances CAR-T cell antitumor activity by preserving their stem cell memory phenotype. CAR-T cells that are less differentiated or less exhausted are more effective [348]. mTOR inhibition is also being exploited for improvement of vaccine strategies.…”
Section: Immunotherapymentioning
confidence: 99%
“…In vivo CRS studies used female SCID-Beige mice injected using 310 6 Raji GFP/Luc cells, following with intraperitoneal injections of C-miR146a (5mg/kg) or PBS daily for three days before transfer of 12.510 6 mock-transfected or CD19-specific CAR-T-cells described before. 15,23,24 Human AML xenotransplants NSG-SGM3 mice were injected intravenously with 210 6 of HL-60 LUC cells and tumor progression was monitored using BLI/AmiX (Spectral Instruments). Mice were injected retro-orbitally with 10mg/kg of C-miR146a or C-scrRNA every other day.…”
Section: Cytokine Release Syndrome Modelsmentioning
confidence: 99%